The effect of photon energy on dose distribution in volumetric-modulated arc therapy planning for head and neck cancer. Issue 3 (14th September 2021) - Nguyen, Trang Hong Thi; Takemura, Akihiro; Ueda, Shinichi; Noto, Kimiya; Kojima, Hironori; Isomura, Naoki
Abstract: Aim: To investigate the effect of different energies on dose distribution in volumetric-modulated arc therapy (VMAT) plans for head and neck cancer. Materials and methods: Data from nine patients undergoing VMAT plans using 6 MV, 10 MV and dual-energy X-ray beams with the Pinnacle 3 V 9.10 treatment planning system (Philips Medical System, Fitchburg, WI, USA) were analysed for quality using the conformity index (CI) and homogeneity index (HI) for planning target volume (PTV), and for mean and maximum dose to the organs at risk (OARs): parotid glands, brainstem, spinal cord and optic nerves. Results: There were no clear differences in the HIs of the PTV dose among the different plans. The CIs for 10 MV and dual-energy VMAT plans were superior to that of the 6 MV VMAT plan (0·8 ± 0·3, 0·8 ± 0·3, and 0·7 ± 0·2, respectively; p = 0·001). There were no significant differences in mean/maximum dose to the OARs among the three VMAT plans. Findings: Compared with the 6 MV VMAT plan, the dual-energy VMAT plan slightly increased the coverage of the PTV with the prescribed dose but did not decrease dose to the OARs.